Digital capital : a bourdieusian perspective on the digital divide - Ragnedda, Massimo; Ruiu, Maria Laura (Emerald Publishing Limited, 2020)
Starting from the assumption that digital capital is a capital in its own right, and can be quantified and measured as such, the authors of this book examine how digital capital can be defined, measured and impact policy. Using the Bourdieusian lens, this book makes a critical contribution to the field by examining in depth the notion of digital capital and by introducing a new theoretical toolkit in order to fully conceptualise it. Against this theoretical background, the authors propose a set of indicators that can be used to measure digital capital at an individual level. Ultimately, readers will learn how this can be used by policy makers to tackle social inequalities which are based on the digital exclusion of citizens.- Resumé vydavatel
Keywords: internet -- ekonomické aspekty; sociální nerovnost; Internet -- economic aspects; social inequality; digitální propast; elektronické knihy; monografie; electronic books; monographs